PERAN GURU DALAM MENINGKATKAN KREATIVITAS ANAK USIA DINI MELALUI KEGIATAN MELIPAT KERTAS ORIGAMI PADA ANAK USIA 5 - 6 TAHUN D I PAUD AKHLAK MULIA KECAMATAN BAROS KABUPATEN SERANG BANTEN - Hamidah, Siti; Maliki, Budi Ilham (LPPM Universitas Bina Bangsa, 2024)
The creativity of folding origami paper is an excellent activity to stimulate creativity and build children's thinking power. Realizing this, the author chose to try to teach several methods of folding origami paper to young children at PAUD Akhlak Mulia, Baros Serang District, Banten. The author deliberately held this activity considering the number of children who appear to have not had any activities that stimulate the development of children's creativity taught at the Akhlak Mulia PAUD. This research aims to find out whether origami paper folding activities can develop children's creativity in PAUD Akhlak Mulia, Baros Serang District, Banten. This type of research is qualitative research. The research subjects were children Group B, which consisted of 20 children, consisted of 9 boys and 11 girls. The data collection methods used were observation, documentation and interviews. The indicator of success that is set is if at least 85% of 20 children are successful in the paper folding game origami with very well developed criteria. The results of the research show that children's origami paper folding games can develop children's creativity and increase after action through origami. At first glance the child looks passive. The two children's footing is more enthusiastic and developing well. These learning gains show that the creativity of group B children with very good criteria has achieved indicators of success